On the flash fire of stratified cloud of liquefied natural gas. (February 2022) - Carboni, Mattia; Pio, Gianmaria; Mocellin, Paolo; Vianello, Chiara; Maschio, Giuseppe; Salzano, Ernesto
Abstract: This work was focused on the characterization of flash fire scenarios resulting from the accidental release of liquefied natural gas (LNG) by keeping into account vapour stratification and temperature gradient, which deeply modify the combustion phenomena for the standard homogeneous cloud. An open-source computational fluid dynamic (CFD) tool was used to this aim, provided premixed and diffusive/convective modification for the combustion model. The effects of the source model for the evaporation and the representative boundary conditions (wind velocity, heat flux from the substrate, relative humidity of the atmosphere, liquid pool diameter) were investigated. The heat flux from the substrate was found the most impacting parameter since it considerably helps vertical spreading, thus reducing the stand-off distances. The comparison with standardized procedures for the consequence assessment of flash fire highlights that the latter approach provides non-conservative results under certain circumstances. Hence, the adoption of the presented procedure is suggested. Considering the nature of the investigated scenario, the effects of thermal and mass stratifications on combustion efficiency were analysed too. As a result, the safety distances calculated by CFD for stratified mixtures were found almost double than the corresponding values estimated for homogeneous cloud and by integral models, commonly adopted in risk analyses. Highlights: Implementation of CFD to characterize a stratified vapour cloud of liquefied natural gas. Evaluation of the effects of boundary conditions on consequences. Comparison of combustion phenomena in case of stratified and homogeneous clouds. Assessment of the stand-off distances for non-homogeneous flash fire.